PHENOTYPIC CHARACTERIZATION OF MODERATE HALOPHILIC FUNGI FROM ATHALASSOHALINE LAKE IN SAUDI ARABIA - Mohammed, Abdul Hafeez; Tantry, Bilal Ahmad; Rahiman, Shaik (European Scientific Journal, ESJ, 2014)
The isolation of moderate halophilic fungi from the Dowmatal Jandal Lake reported here for the first time. In 2000, Fungi were first reported to thrive in solar salterns . The mycobiota of the Dowma lake in this study, was dominated by Aspergillus, Penicillium and Rhizomucor, where Mucor was found in lesser numbers. Aspergillus and Penicillium genera were obtained from the water sample, while Rhizopus and Mucor were obtained from the sediment samples. There was a significant difference in the growth of each isolate at different salt concentrations. The isolates are P.Chrysogenum , A. flavus, A. fumigatus, Mucor sp., Mucor circinelloides and Rhizomucor sp. In the present study, we assessed their growth at a wide range of salinity (0 to 25% NaCl ). Furthermore, isolates were found in greater numbers in the sediment sample as compared to that in the water sample. The obligate moderate halophiles isolated, belonged to the genus Aspergillus and were identified as A. flavus and A fumigatus. However, we believe that all the six isolates are suitable model organisms to study halotolerance in eukaryotes.